What should be the primary target of "treat to target" in psoriatic arthritis? - Coates, LC; Lubrano, E; Perrotta, FM; Emery, P; Conaghan, PG; Helliwell, PS (Journal of Rheumatology, 2018)
Background Treat to Target in psoriatic arthritis (PsA) recommendations have stated that the target should be remission or inactive disease. Potential definitions include Very Low Disease Activity (VLDA), PsA Disease Activity Score (PASDAS) near remission, Disease Activity in PsA (DAPSA) or clinical DAPSA remission. Our aim was to investigate the proportion of patients who fulfil these definitions and how much residual active disease remained. Methods This analysis used two datasets: firstly, trial data from the Tight Control of PsA (TICOPA) study which included 206 patients with recent onset (<2 years) PsA receiving standard and biological DMARDs; and secondly an observational clinical dataset from Italy of patients receiving biological DMARDs. Proportions achieving each of the four potential targets were calculated in each dataset and comparisons between treatment groups were performed in the TICOPA dataset. Levels of residual disease were established for key clinical domains of PsA. Results All measures could differentiate the TICOPA trial treatment groups (p<0.03). Lower proportions of patients fulfilled the VLDA criteria compared to DAPSA or cDAPSA remission. PASDAS results were different between the cohorts. Residual active disease was low across all definitions although higher levels were seen in DAPSA and cDAPSA compared to VLDA, particularly for psoriasis. In all measures, the proportion with elevated CRP was similar and low. Conclusions VLDA appears the most stringent measure. It ensures that significant active arthritis, enthesitis and psoriasis are not present in contrast with DAPSA and PASDAS where composite scores can ‘hide’ active disease in some domains.